Pengaruh Profitabilitas Terhadap Nilai Perusahaan: Moderasi Pengungkapan Corporate Social Responsibility - Rika Surianto Zalukhu; Rapat Piter Sony Hutauruk; Daniel Collyn (Accounting Progress, 2026)
This study aims to analyze the effect of profitability on firm value and the role of Corporate Social Responsibility (CSR) disclosure in moderating this relationship in consumer cyclicals sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This study employed a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sampling technique used was purposive sampling, resulting in 15 companies that met the research criteria. Data analysis was conducted using panel data regression analysis and Moderated Regression Analysis (MRA). The results indicate that profitability has a positive and significant effect on firm value. In addition, CSR disclosure is proven to moderate the effect of profitability on firm value by strengthening the relationship. These findings suggest that investors not only consider a company’s ability to generate profits, but also pay attention to the company’s commitment to social responsibility and business sustainability. The implications of this study indicate that companies need to maintain a balance between achieving financial performance and implementing CSR in order to enhance investor confidence and strengthen firm value.